Metaphors of Life in Bhagavad Gita As It Is - Sisiana Dewi, Ni Luh Putu (Humanis; Vol 22 No 2 (2018), 2018)
Metaphors are frequently used in everyday conversation unconsciously. People deliver the metaphoric expressions underlaid by conceptual metaphor that consists of the target and source domains. This study aims to find out the types of metaphorical expressions and analyze the conceptual metaphors underlaying the metaphorical expressions. The data were generated from Bhagavad Gita text using a corpus machine named AntConc 3.4.4w. With the corpus method and AntConc, 690 sentences containing metaphors of life were found. These data were analyzed by applying the conceptual metaphor theory of Lakoff and Johnson (2003) and Steen (2007).The result of the study shows that the metaphorical expressions of  life in Bhagavad Gita are covered in all types of metaphor, they are: Structural, Ontological (along with its subsection that is Personification), and Orientational metaphors. In Bhagavad Gita, there are 24 conceptual metaphors that underlay the metaphorical expressions. The most frequently found conceptual metaphors were LIFE IS AN ENTITY, LIFE IS A JOURNEY and LIFE IS A CONTINUOUS ACTIVITY.